Enzymatic Spermine Metabolites Induce Apoptosis Associated with Increase of p53, caspase-3 and miR-34a in Both Neuroblastoma Cells, SJNKP and the N-Myc-Amplified Form IMR5 - Yuta Kanamori; Alessia Finotti; Laura Di Magno; Gianluca Canettieri; Tomoaki Tahara; Fabio Timeus; Antonio Greco; Paola Tirassa; Jessica Gasparello; Pasquale Fino; Carlo Maria Di Liegro; Patrizia Proia; et al. (Cells, 2021)
Neuroblastoma (NB) is a common malignant solid tumor in children and accounts for 15% of childhood cancer mortality. Amplification of the N-Myc oncogene is a well-established poor prognostic marker in NB patients and strongly correlates with higher tumor aggression and resistance to treatment. New therapies for patients with N-Myc-amplified NB need to be developed. After treating NB cells with BSAO/SPM, the detection of apoptosis was determined after annexin V-FITC labeling and DNA staining with propidium iodide. The mitochondrial membrane potential activity was checked, labeling cells with the probe JC-1 dye. We analyzed, by real-time RT-PCR, the transcript of genes involved in the apoptotic process, to determine possible down- or upregulation of mRNAs after the treatment on SJNKP and the N-Myc-amplified IMR5 cell lines with BSAO/SPM. The experiments were carried out considering the proapoptotic genes Tp53 and caspase-3. After treatment with BSAO/SPM, both cell lines displayed increased mRNA levels for all these proapoptotic genes. Western blotting analysis with PARP and caspase-3 antibody support that BSAO/SPM treatment induces high levels of apoptosis in cells. The major conclusion is that BSAO/SPM treatment leads to antiproliferative and cytotoxic activity of both NB cell lines, associated with activation of apoptosis.